KEUNTUNGAN DAN KERUGIAN PENGGUNAAN METODE GROSS-UP DALAM PERHITUNGAN PPh PASAL 21 PEGAWAI TETAP MELALUI ANALISA PERBANDINGAN - Marfiana, Andri (Jurnal Pajak dan Keuangan Negara (PKN), 2019)
This research aims to show a comparative between Gross-Up method with others method to calculate article 21 income tax in order to tax planning action. Moreover, this journal gives a tutorial, how to calculate Article 21 Income Tax, use Gross-Up method in Ms Excel and e-SPT aplication. This research uses descriptive and tutorial method to discuss research questions. The result shows that the implementation of Gross-Up method in calculating article 21 income tax, only gives optimal result if implemented to employees who has salary below company tax rate. Contrary,Â  the result will be minumum if used to employees who have higher tax rate. However, income tax benefit that give to employees can increase a motivation among them.In this study, it is argued that the implementation of Gross-Up method can be optimal in situational cases.